Hormonal Regulation of Programmed Cell Death in Sea Urchin Metamorphosis - Wynen, Hannah; Heyland, Andreas (Frontiers in Ecology and Evolution, 2021)
Programmed cell death (PCD) has been identified as a key process in the metamorphic transition of indirectly developing organisms such as frogs and insects. Many marine invertebrate species with indirect development and biphasic life cycles face the challenge of completing the metamorphic transition of the larval body into a juvenile when they settle into the benthic habitat. Some key characteristics stand out during this transition in comparison to frogs and insects: (1) the transition is often remarkably fast and (2) the larval body is largely abandoned and few structures transition into the juvenile stage. In sea urchins, a group with a drastic and fast metamorphosis, development and destruction of the larval body is regulated by endocrine signals. Here we provide a brief review of the basic regulatory mechanisms of PCD in animals. We then narrow our discussion to metamorphosis with a specific emphasis on sea urchins with indirect life histories and discuss the function of thyroid hormones and histamine in larval development, metamorphosis and settlement of the sea urchin Strongylocentrotus purpuratus. We were able to annotate the large majority of PCD related genes in the sea urchin S. purpuratus and ongoing studies on sea urchin metamorphosis will shed light on the regulatory architecture underlying this dramatic life history transition. While we find overwhelming evidence for hormonal regulation of PCD in animals, especially in the context of metamorphosis, the mechanisms in many marine invertebrate groups with indirect life histories requires more work. Hence, we propose that studies of PCD in animals requires functional studies in whole organisms rather than isolated cells. We predict that future work, targeting a broader array of organisms will not only help to reveal important new functions of PCD but provide a fundamentally new perspective on its use in a diversity of taxonomic, developmental, and ecological contexts.